2021
DOI: 10.3390/biom11121767
|View full text |Cite
|
Sign up to set email alerts
|

Amazonian Bacuri (Platonia insignis Mart.) Fruit Waste Valorisation Using Response Surface Methodology

Abstract: Bacuri (Platonia insignis Mart) is a species from the Clusiaceae genus. Its fruit pulp is commonly used in South America in several food products, such as beverages, ice cream and candies. Only the pulp of the fruit is used, and the peels and seeds are considered waste from these industries. As a trioxygenated xanthone source, this species is of high interest for bioproduct development. This work evaluated the mesocarp and epicarp of bacuri fruits through different extraction methods and experimental condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Industrial processing transforms fruits into commercially attractive byproducts (such as juices, jams, jellies, pickles, and natural flavors) and also generates significant amounts of different wastes such as peel, seed, pomace, pulp, stem, and others not directly used in human food but discarded as waste. 8,52,53 Although reported differently by different researchers, this accounts for nearly half of the fruit by weight. For instance, the findings of Han et al, 13 found that papaya fruit processing generates a large amount of papaya waste in which seed waste constitutes up to 30% of the papaya by volume.…”
Section: Tropical Fruit-processing Waste/ Byproducts and Compositionmentioning
confidence: 92%
See 3 more Smart Citations
“…Industrial processing transforms fruits into commercially attractive byproducts (such as juices, jams, jellies, pickles, and natural flavors) and also generates significant amounts of different wastes such as peel, seed, pomace, pulp, stem, and others not directly used in human food but discarded as waste. 8,52,53 Although reported differently by different researchers, this accounts for nearly half of the fruit by weight. For instance, the findings of Han et al, 13 found that papaya fruit processing generates a large amount of papaya waste in which seed waste constitutes up to 30% of the papaya by volume.…”
Section: Tropical Fruit-processing Waste/ Byproducts and Compositionmentioning
confidence: 92%
“…Global trade and processing of tropical fruits are increasing significantly 5,8,51 . The consumption of fresh fruits for their refreshing taste and nutritional value has been common for a long time but the use of processed fruit products has become a fashion and is expanding due to an increase in fruit processing and preserving technologies.…”
Section: Tropical Fruit‐processing Waste/byproducts and Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10] Essa atividade está relacionada aos seus constituintes químicos com propriedades antioxidantes como a vitamina C (ácido ascórbico) evitaminaE (tocoferóis), flavonoides, antocianinas e polifenóis. 11 Outros benefícios do consumo do Bacuri estão relacionados a diversos fatores, sobretudo pelo teor de ácidos graxos. Neste sentido, o estudo fitoquímico relacionado às cascas do fruto indicam a presença de vários compostos como os ácidos palmítico, oleico, linoleico, esteárico, caprílico e mirístico, álcoois, hidrocarbonetos e ésteres.…”
unclassified